PENGARUH PERKEMBANGAN ASTROPOLITIK TERHADAP KEBIJAKAN KEAMANAN DAN PERTAHANAN AMERIKA SERIKAT PADA MASA KEPEMIMPINAN DONALD TRUMP (2018-2020) - Kun Dhayita H. Mahardhika; Nuriyeni K. Bintarsari; Arif Darmawan (UIN ALAUDDIN MAKASSAR, 2022)
Astropolitics is a focus of study that defines the interrelationship of the space field, technology, and the development of political, military, and strategic policies. In this era, astropolitics became field of interest for some countries in the world especially developed countries, including the United States. Therefore, the United States formed a space force that aims to avoid the threat of outer space and guard the territory. This was done by the United States because the outer space domain was considered to be one of the new domains of terrestrial war, which was also intended as an arena for the race for ballistic missiles and military navigation satellites. The formation of the United States Space Forces is also the response of the United States government under the leadership of Donald Trump to the development of missile defense technology and space military which was also developed by Russia and China.